Dari Folklore ke Wisata: Menelusuri Seni Tradisi Ranuyoso sebagai Ikon Budaya - Eka, Scarletina Vidyayani; Hamamah; Nurmansyah, M. Andhy; Setiawan, Fredy Nugroho; Nufiarni, Rizki (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Ranuyoso village in Lumajang has natural and cultural potentials that can be developed to natural, agro and traditional tourism area. Specifically, the community service aimed to develop the potential aspects of Ranuyoso's traditional arts. The project focused on documenting folklore and traditional arts to support Ranuyoso tourism. The problems that were attempted to be solved were: (1) what were traditional arts and local culture that can be documented in order to support the tourism village that will be created; and (2) what were the traditional arts that can become the tourism icon of Ranuyoso village. From the results of the service that had been carried out in Ranuyoso village, the documentation of Ranuyoso's original art was obtained, namely the art of jaran kencak, slempang dance (kopyah dance), glipang dance and kenong telok. From the results of mapping and documentation, Jaran Kencak was chosen as the tourism icon of Ranuyos.